Reformational Insights for the Study of International Relations - Chaplin, Jonathan (Philosophia reformata, 2015)
This essay presents a brief overview of selected insights deriving from reformational social and political philosophy, especially that of Herman Dooyeweerd, relevant to the study of international relations. Three clusters of potentially fruitful reformational concepts are identified. These relate to, first, the nature of the discipline of International Relations; second, the “structural purpose” of the state and other political entities; third, the plural, non-state actors of global civil society. It is proposed that distinctively reformational insights can offer illuminating orientations towards, or at least pose valuable research questions confronting, the development of a Christianly-informed ir theory today.